Character - Kazan, Nicholas; Attanasio, Paul; First Light Video Publishing; The Writers Guild Foundation; TMW Media Group, Inc. ([California] : The Writer Guild Foundation : TMW Media Group, Inc. (distributor), 2004)
Lear the mystery of character, how character dictates the plot, character information, biographies, real characters vs. fictional characters, writing a franchise character, rules to break and not to break
Title from title screen
Tape 2: Character
Photography, Andrea Cimini
Keywords: Character and characteristics in motion pictures; Motion picture authorship